Indigenous use and conservation of harbor seals (Phoca vitulina) at Yakutat, Alaska since the sixteenth century - Crowell, Aron L.; Ramos, Judith Daxootsú; Etnier, Michael A. (Frontiers in Environmental Archaeology, 2024)
Sustainable Indigenous resource use reflects balance between animal populations and levels of human consumption, influenced by natural cycles of faunal abundance, community size and subsistence needs, procurement technologies, and the requirements of trade or commodity production. Sustainability is “epiphenomenal” when animal populations are preserved, and community needs met, without deliberate measures to prevent overharvesting. Alternatively, Indigenous conservation—cultural practices that moderate use of a resource to prevent its depletion—may play a determinative role. In this study from the Tlingit community of Yakutat, Alaska in the Northwest Coast cultural region, we interweave Indigenous and scientific perspectives to trace the use and conservation of harbor seals (Phoca vitulina) from before Western contact through the Russian and American colonial periods to the present. Harbor seals, which concentrate in large numbers at a summer ice floe rookery near Hubbard Glacier, are the community's most important subsistence food and a key to its culture and history. The Smithsonian Institution and Yakutat Tlingit Tribe undertook collaborative research in historical ecology and archaeology in 2011–2014 including oral interviews with elders and subsistence providers, excavations at sealing sites, archaeofaunal analysis, historical and archival research, and consideration of climate cycles and biological regime shifts that influence the harbor seal population in the Gulf of Alaska. We compare technologies and hunting practices before and after Western contact, estimate harvest levels in different periods, and evaluate the effectiveness of traditional conservation practices that included hunting quotas enforced by clan leaders and the seasonal delay of hunting with firearms to prevent abandonment of the rookery by the seal herd.